Unexpected High-Substrate-Dependent Ketonization of Aldose on Niobium Phosphate-Supported Magnesia: An Emphasis on Surface Chemisorption - Gao, Da-Ming; Zhang, Shuoqi; Lei, Tingzhou; Zhu, Jie; Huhe, Taoli; Sun, Fuan; Zeng, Guixiang; Liu, Haichao (Industrial & engineering chemistry research, 2022)
A water-tolerant magnesia-based solid base was prepared by combining the use of a non-equilibrium and highly structured dual-porous niobium phosphate (NbP) as the support and high-temperature thermal treatment. The crystal growth of MgO changed, and the bond length of Mg–O was longer than that of pure MgO after it was supported on NbP, which led to the higher basic property of O2– on the surface of MgO/NbP to act as a solid base catalyst toward aldose ketonization. It was revealed that the prepared solid base MgO/NbP exhibited high substrate dependence for ketonization of saccharides, facilitating the use of glucose and glucose-containing aldo-disaccharidesincluding maltose, cellobiose, lactose, and melibiosedue to their lower free energy after chemisorption than that of pentose, and a moderate reverse reaction barrier in aqueous solution. It was demonstrated that ketonization mainly occurred on the solid surface, especially in the case of high substrate concentration, which was different from the conventional opinion. The type of glycosidic bond and the constituent monosaccharides also affected the yield and selectivity of rare keto-disaccharides. The high performance of the MgO/NbP catalyst toward ketonization of disaccharides was realized as the typical yield and the productivity of maltulose reached 14.2% and 42.6 g·kg-solution–1·h–1, respectively, when treated with 30.0 wt % maltose solution at 130 °C. Although deactivation issues, such as leaching of ions and coke deposition, still remain to be solved, the catalyst has potential to be used in synthesizing high-value rare keto-disaccharides.